Perception among Secondary School Students towards Bully and Bully-Victim in Kuala Terengganu, Malaysia. - Lukman@Zawawi, Mohamad; Azlini, Chik; Normala, Riza (2018)
This research is an overview of the perception among secondary school students in Kuala Terengganu on bullying issues, covering the characteristic of bullies and victims. The research was involved in descriptive statistics and exploratory analysis. A total of 405 participants from secondary school students around the Kuala Terengganu area responded to the questionnaire. The research found that more male students were involved in bullying cases than female students. The research found that the characteristic of bullies included having problems in academic, family problems, smoking, and indiscipline, especially among senior students. The researchers also found that bullieswanted to show that they are powerful and domineering while emotionally torturing their victims. The characteristic of bully victims such shy, lonely and from a lower socio-economic background. It is hoped that these results can assist the authorities in improving the existing laws and more effective.